Analysis of switched capacitor networks - Savacı, F. Acar. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1982., 1982)
In this thesis, after introducing the advantages of switched capacitor (SC) networks, several time-domain analys methods of SC networks have been investigated and compared. with each other. An efficient method for the solvability problem, which is very important for network analyzers, has also been given. The z-domain analysis of SC networks is given.by introducing z-domain equivalent circuits which are very basic tools for network designers. The z-domain analysis is built on the time-domain signal processing. mechanism of SC network Finally, frequency domain analysis of SC networks and their filtering properties have been investigated. The examples given in the thesis cari clarify all the introquced methods.
Keywords: Switched capacitor circuits.